The Relationship Between Patient Characteristics, Nurse Response Time, and Emergency Room Patient Satisfaction in Manggarai Regency - Krowa, Yuliana Reginaldis Rosali; Mariati, Lusia Henny; Meku, Fransiskus Xaverius (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
The quality of nursing services has a significant impact on patient satisfaction, particularly in influencing the decision to return for future care. In the emergency department, nurses are expected to work swiftly, accurately, and efficiently—where response time becomes a critical factor influencing patient satisfaction. This study aimed to examine the relationship between patient characteristics and nurse response time on patient satisfaction in the Emergency Department of Manggarai Hospital. Data were analyzed using univariate analysis and logistic regression. The findings showed no significant relationship between patient characteristics and satisfaction (p = 0.719). However, nurse response time was found to have a significant relationship with patient satisfaction (p = 0.001).